Scary Godmother. The revenge of Jimmy [videorecording (DVD)] - Norton, Ezekiel; Buckley, Bob (Anchor Bay Entertainment, 2005)
Sequel to Scary Godmother Halloween Spooktacular. The Godmother and Hannah try to protect Halloween from Hannah's mean cousin, Jimmy. Last Halloween Jimmy learned that monsters really do exist and he's sure they are coming to get him.